The relevance of primary dealers for public bond issues - Wolfgang Breuer (Goethe University Frankfurt, Center for Financial Studies (CFS), 1999)
We analyze the role of different kinds of primary and secondary market interventions for the government's goal to maximize its revenues from public bond issuances. Some of these interventions can be thought of as characteristics of a primary dealer system. After all, we see that a primary dealer system with a restricted number of participants may be useful in case of only restricted competition among sufficiently heterogeneous market makers. We further show that minimum secondary market turnover requirements for primary dealers with respect to bond sales seem to be in general more adequate than the definition of maximum bid-ask-spreads or minimum turnover requirements with respect to bond purchases. Moreover, official price management operations are not able to completely substitute for a system of primary dealers. Finally it should be noted that there is in general no reason for monetary compensations to primary dealers since they already possess some privileges with respect to public bond auction.
urn:nbn:de:hebis:30-9609
Keywords: G18; H63; 330; public bonds; primary dealers; official market interventions; bond auctions; market makers